Novel techniques for preventing bacterial attachment to foods and food-processing surfaces - Wang, Y.; Dykes, Gary (CRC PRESS-TAYLOR & FRANCIS GROUP, 2014)
© 2015 by Taylor & Francis Group, LLC. Bacteria must attach to surfaces in order to move through the food chain and cause human disease or food spoilage. These surfaces may be abiotic, such as those associated with processing equipment, or biotic, such as those associated with food itself. Preventing bacterial attachment and removing already attached bacteria are important aspects of good hygiene and cleaning practice. The current practice to achieve this generally entails the use of synthetic surfactants. This approach is not always effective and suffers from the drawback of creating a potentially negative impact on the environment. For this reason, a number of alternative methods for controlling bacterial attachment are being investigated.